Voluntary participation in residents association: a proposed study at a matured township / Mahadzir Ismail ...[et al.] - Ismail, Mahadzir; Ismail, Junaida; Harun, Etty Harniza; Abdul Jalil, Muna (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
This paper scrutinizes the voluntary participation in the residents’ association at Bandar Laguna Merbok, a matured township in Kedah. This study defines voluntary participation as a community’s voluntary involvement in Persatuan Penduduk Laguna Merbok (PPLM). This study aims to understand how the individuals decide to participate voluntarily in PPLM and to determine the factors behind their partic ipation. This study will employ a basic survey instrument. The residents are set to undertake an online survey to rate their voluntary participation perceptions towards the PPLM. Their feedback will be gathered and analyzed using correlational analysis. P urposive Sampling Technique is employed to collect data from targeted respondents. It is hoped that this study will be beneficial to PPLM in terms of promoting their services and attracting more membership in the future.